Prophetic Parenting Pola Asuh Orangtua Dalam Pembentukan Karakter Anak Usia Dini - M. Rizqon Al Musafiri; Nur Miftahurrohmah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
This research is motivated because children at an early age are no longer traditional games, but electronic goods such as cellphones, games, and others, even children are good at accessing the internet. this will affect the formation of character in children when they grow up, and will make the next generation fade the nobility of Indonesia. The focus of this research is how the Prophetic Parenting process in character building how Parenting Parenting Model in Formation of Early Childhood Characteristics. The purpose of this study is to answer how the process of prophetic parenting and parenting models from the research focus. The theory used in this research is the theory of Prophetic Parenting by using the Prophetic Parenting method as a foundation in the formation of children's character from an early age. The method used in this study is a qualitative method. This study focuses on a technique that is used as a model for parenting in the formation of character in children. While the type of research used is descriptive qualitative.